Nasal septum ulcer as an isolated manifestation of histoplasmosis - Pedroso, Maria C.M. (IDCases, 2019)
Histoplasmosis is an infection caused by the dimorphic fungus Histoplasma capsulatum, which is saprophyte of contaminated soil. In the immunocompetent host, the symptoms of histoplasmosis tend to be mild or even non-existent. In immunocompromised patients, the manifestations may be more severe and the disease manifests itself in a disseminated form, with high mortality rates. Isolated mucosal lesions are infrequent and the purpose of this report is to describe an unusual case of nasal septum ulcer as an isolated clinical manifestation of the disease.